PERANCANGAN BUKU ILUSTRASI DIGITAL TARI PENDET SEBAGAI UPAYA PELESTARIAN BUDAYA BALI UNTUK ANAK USIA 6-12 TAHUN - Hartono, Caroline Inge; Rahmadianto, Sultan Arief; Sukmaraga, Ayyub Anshari (Ma Chung Press, Universitas Ma Chung, 2025)
Pendet dance is a sacred dance originating from Bali and has very high cultural value. However, in the current digital era, children's knowledge and interest in Balinese culture, especially the Pendet Dance, is starting to decrease. Therefore, there needs to be an effort to preserve Balinese culture in a way that is interesting and easily accessible to children. This research aims to design a digital illustration book about Pendet Dance as a medium for learning and preserving Balinese culture for children aged 6-12 years. This book is designed with attractive illustrations and is equipped with informative text so that it is easy for children to understand. The research method used is a qualitative method with a design approach. Data collection techniques were carried out through observation, questionnaires, literature studies and documentation studies. Meanwhile, the analysis method used in the design process is 5W + 1H with a cyclic strategy. Apart from that, this book can also function as a learning medium for children about the noble values of Balinese culture.